Feelings of structure : explorations in affect - Engle, Karen, 1974-; Wong, Yoke-Sum (McGill-Queens University Press, 2018)
"Sweatsuits and the apocalypse, the demands of a sofa, a life recalled through window frames, whale watching through cancer, the serendipity of geographical names ... In Feelings of Structure, these are just some of the spaces and places, memories, and experiences addressed by the authors in writings that are multilevel explorations of the tangled-up nature of feeling and structure. Inspired by Raymond Williams's classic essay, "Structures of Feeling" and influenced by the current discussion of affect studies, this collection inverts Williams's influential concept to explore the ephemerality of feeling as working in concert with the grounding forces of materiality and history. Feelings of Structure is a collection of twelve original texts that explores the weight of diverse encounters with a variety of configurations, be they institutional, spatial, historical, or fantastical. Featuring writers from a variety of disciplines, this book aims for textual evocation in subject matter and approach, with essays that encompass multiple methodologies, writing styles, and tones. Experimental in nature, Feelings of Structure balances between the need for concrete and specific observation with the ephemerality of experience."--